Invasiveness risk of the tropical biofuel crop Jatropha curcas L. into adjacent land use systems: from the rumors to the experimental facts. Issue 4 (16th October 2012) - Negussie, Aklilu; Achten, Wouter M. J.; Aerts, Raf; Norgrove, Lindsey; Sinkala, Thomson; Hermy, Martin; Muys, Bart
Abstract Jatropha curcas L. produces seeds rich in non‐edible oil suitable for biodiesel but it has been categorized as invasive. Although not scientifically verified, this allegation has resulted in a cultivation ban in several countries. In this article we report an integrated series of observations and experimental findings from invasiveness research in Zambia. We studied the impacts of J. curcas plantations on adjacent land use systems focusing on spontaneous occurrence of seedlings, seed dispersal mechanisms, seed predation by animals, and germination success of dispersed seeds. No spontaneous regeneration was observed in land use systems adjacent to J. curcas plantations. Primary seed dispersal was limited, predominantly under the canopy of the mother plant. Rodents and shrews dispersed and predated J. curcas seeds and fruits. They transported the seeds up to 23 m from the sources and repositioned them in their burrows up to 0.7 m deep, but none of these seeds could establish. Germination experiments in adjacent land use systems revealed 4% germination success at the soil surface, and 65% if buried artificially at 1–2 cm depth, yet the latter is unlikely to occur under natural conditions. These findings show that J. curcas seeds may be dispersed by animals to adjacent land use systems, but no natural recruitment was observed given low germination on the surface and none in burrows. Altogether these results suggest that the plant currently does not show an elevated risk of invasion to adjacent land use systems, at least in the investigated case study. But more long‐term studies, also in other growing areas are needed to corroborate these results.